2013
DOI: 10.1016/j.ejmp.2012.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Control of the temperature rise in magnetic hyperthermia with use of an external static magnetic field

Abstract: Our purpose in this study was to investigate the usefulness of a method for controlling the temperature rise in magnetic hyperthermia (MH) using an external static magnetic field (SMF), and to derive an empirical equation for describing the energy dissipation of magnetic nanoparticles (MNPs) in the presence of both the alternating magnetic field (AMF) and SMF through phantom experiments. We made a device that allows for MH in the presence of an SMF with a field-free point (FFP) using a Maxwell coil pair. We me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 29 publications
4
61
0
1
Order By: Relevance
“…We investigated the effect of SMF on the temperature rise in magnetic hyperthermia using this device and then evaluated the feasibility of controlling the temperature rise using an SMF with an FFP under various conditions of the AMF and SMF. Our experimental results demonstrated that the SLP value (referred to as "SAR" in our previous paper [16]) decreased with increasing H s [16]. Thus, the present results shown in Figure 4 to Figure 6 appear to support our experimental results [16].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…We investigated the effect of SMF on the temperature rise in magnetic hyperthermia using this device and then evaluated the feasibility of controlling the temperature rise using an SMF with an FFP under various conditions of the AMF and SMF. Our experimental results demonstrated that the SLP value (referred to as "SAR" in our previous paper [16]) decreased with increasing H s [16]. Thus, the present results shown in Figure 4 to Figure 6 appear to support our experimental results [16].…”
Section: Discussionsupporting
confidence: 82%
“…This device can also generate an FFP and move it by varying the DC electric currents applied to the individual Maxwell coils [16]. We investigated the effect of SMF on the temperature rise in magnetic hyperthermia using this device and then evaluated the feasibility of controlling the temperature rise using an SMF with an FFP under various conditions of the AMF and SMF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For fitting this behaviour, a linear function is usually used [30] but also a Box-Lucas function has been proposed to extract the SPA values. [35,37] The initial increase of temperature can be extracted from (dT/dt)max so that a standardized protocol for calculating the SPA can be given.…”
Section: Resultsmentioning
confidence: 99%